2010
DOI: 10.1542/peds.2009-0307
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Holiday-Related Injuries Presenting to US Emergency Departments

Abstract: Most injuries that were sustained on holidays and required ED treatment were not holiday-specific but were associated with more general activities. Parents should be aware that holidays present a risk not only for holiday-specific injuries but also for more general, "everyday" injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
4
14
1
Order By: Relevance
“…Other studies also showed that burns and lacerations were the most common types of injury. 7,8,21-23,24 According to our data, about 82% of injured patients were treated as outpatients and approximately 18% were hospitalized, which is in line with the results of similar studies. 20,21 Witsaman et al (2006) found that in the USA, 91.6% of children referred to hospitals for fireworks-related injuries were treated in the emergency department and discharged without inpatient hospitalization, whereas 5.3% were hospitalized and 2.3% were transferred to another institution.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies also showed that burns and lacerations were the most common types of injury. 7,8,21-23,24 According to our data, about 82% of injured patients were treated as outpatients and approximately 18% were hospitalized, which is in line with the results of similar studies. 20,21 Witsaman et al (2006) found that in the USA, 91.6% of children referred to hospitals for fireworks-related injuries were treated in the emergency department and discharged without inpatient hospitalization, whereas 5.3% were hospitalized and 2.3% were transferred to another institution.…”
Section: Discussionsupporting
confidence: 91%
“…In our study we found that boys had higher rates of TBI than girls in each age subgroup, according to other studies [15][16][17][18]. It can be explained by greater male risk-taking behaviors and differences in male socialization.…”
Section: Discussionsupporting
confidence: 84%
“…8, 35, 36 It was, however, unexpected and counter to our hypothesis to find lower severity injuries and lower rates of admission or transfer after an injury-related ED visits for non-Hispanic black children compared with non-Hispanic white children and among children from areas with moderate and high prevalence of poverty compared with children from areas with low prevalence of poverty. These results are in contrast with studies that have demonstrated higher rates of severe and fatal injuries in children with lower SES.…”
Section: Discussioncontrasting
confidence: 73%
“…2 Although the CDC has documented declining rates of fatal childhood injuries, 3 national injury surveillance systems show increased pediatric ED visits for specific injuries. 48 …”
mentioning
confidence: 99%